2017
DOI: 10.18535/jmscr/v5i1.94
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Congenital Anomalies in A Tertiary Care Centre

Abstract: Aim of the Study-The aim of this study is to identify the common patterns of anomalies seen in the hospital

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 5 publications
5
6
0
Order By: Relevance
“…6 The male babies were most commonly affected than Female babies, it may be because of the fact that the females were afflicted with more lethal congenital malformations and could not survive to be born with signs of life. The results of our study findings were similar to the study findings of Tapan Pattanaik et al, Bhalerao and Garg, Doddabasappa et al 7,5,8 The age of the mother during pregnancy associated with congenital anomalies in our study showed lea than 25 years were more commonly affected, similar results were also seen in the study done by Tapan Pattanaik et al, and S. Lakshmi Vinodh et al 7,9 The Multigravida Mothers were commonly affected by Congenital anomalies in our study which is comparable to the study findings of Tapan Pattanaik et al, and Bhalerao and Garg. 5,7 In the present study, congenital anomalies were observed in 18.6% of consanguineous marriage and 81.4% of nonconsanguineous marriage, similar results were also seen in the study done by Tapan Pattanaik et al, and Bhalerao and Garg.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…6 The male babies were most commonly affected than Female babies, it may be because of the fact that the females were afflicted with more lethal congenital malformations and could not survive to be born with signs of life. The results of our study findings were similar to the study findings of Tapan Pattanaik et al, Bhalerao and Garg, Doddabasappa et al 7,5,8 The age of the mother during pregnancy associated with congenital anomalies in our study showed lea than 25 years were more commonly affected, similar results were also seen in the study done by Tapan Pattanaik et al, and S. Lakshmi Vinodh et al 7,9 The Multigravida Mothers were commonly affected by Congenital anomalies in our study which is comparable to the study findings of Tapan Pattanaik et al, and Bhalerao and Garg. 5,7 In the present study, congenital anomalies were observed in 18.6% of consanguineous marriage and 81.4% of nonconsanguineous marriage, similar results were also seen in the study done by Tapan Pattanaik et al, and Bhalerao and Garg.…”
Section: Discussionsupporting
confidence: 92%
“…5,7 In the present study, most of the mothers of babies were registered (95.3%) followed by Unregistered (4.7%) which is in contrast to the study findings of Sandya rani et al, where it was seen almost equally in both the groups. 11 The findings of the weight of babies associated with congenital anomalies in our study were similar to the study findings of S Lakshmi Vinodh et al, and Alawad AM et al 6,9 The findings of our study was comparable to the S Lakshmi Vinodh et al Findings where singleton had more incidences of Congenital Anamolies. 9 The involvement of Various systems was seen in our study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings are comparable to similar studies from India, which reported an incidence of 2.72% and 1.9%, 2.48%. [8][9][10] The most common anomaly detected was Central nervous system malformations, 40/75 (53.33%). Many studies have shown that CNS malformations were associated with high perinatal mortality.…”
Section: Discussionmentioning
confidence: 99%